Answer :

LHS



We know that sec (-x) = sec (x) and tan (-x) = -tan (x).




We know that when n is odd, sec cosec and tan cot.


= [-cosecx] [cosecx] - [-cotx] [cotx]


= -cosec2x + cot2x


= - [cosec2x – cot2x]


We know that cosec2x – cot2x = 1


= -1


= RHS


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Find the values oRD Sharma - Mathematics